Mobilt internet för skogsbruket med CDMA2000 i450 MHz - bandet - Håkansson, Björn (SLU/Dept. of Forest Products, 2003)
Improved wireless datacommunication with the forest machines might be the next big step in the logging process. The use for wireless communicationsystems within the forestry is among other things to report the production from the forest machines, to supply the machine opera-tors with the right information and for safety. CDMA2000/ 450 is a third generation mobilecommunicationsystem which could replace the old NMT- 450 and for comparatively low costs. The reason for the low costs is that you only have to use the old NMT- 450 masts and supply them with new equipment. In the test of CDMA2000/450, that has taken place in northern Uppland, two kind of files have been sent. A portable computer was connected to a CDMA2000 mobiletelephone and the files were sent through e- mail to another computer. One file was at about 560kb and con-tained among other things, maps. The other one was a production file from a harvester that only contained about 7kb. The time for sending these files was at most times about 2.30 min-utes except when the transmission took place in the outer parts of the service area where there was a week connection.